A Study of the Magnetic Properties and Structure of Heusler Alloys Prepared by Arc-Melting Technique - Khalefa, N. A. (Science and Technology Indonesia, 2024)
Heusler alloys were prepared in this study using the Arc-Melting method in which 30 g of the Arc-melting pure elements were combusted in an Argon arc furnace. Saturation magnetization, X-ray diffraction (XRD) analysis, and scanning electron microscope (SEM) were used to characterize the prepared alloys in terms of the compositions (Co2TiZ), where Z= Al, Ge, Sb are related IVB sub-group metals. In this work, the specimens containing Ge and Ti have fully Ferro magnetically order and L21 chemical structure with magnetism due to the magnetic moments attributed to the Co site. The Heusler alloys containing IIB or IVB sub-group metals such as Al, Ti, or Ge behave ferromagnetism, with the magnetic moments being attributed to the magnetic moments of the Co sites. Heusler alloys containing the group IVB element such as Sb exhibited vacant chemical effects with Co sites, and they also contain some paramagnetic compounds. Heusler alloys with Sb element exhibited paramagnetic behavior with vacant chemical order. Alloys demonstrate different magnetic properties as a result of temperature change and exchange interaction with atomic structure.